Erkenntnisse zur Beschreibung des aktivierten mathematischen Wissens in empirischen Kontexten an einem Beispiel aus der Wahrscheinlichkeitstheorie (mathematica didactica, 2022)
This article illustrates how the epistemological approach of empirical (student) theories can be used for a description of the development of mathematical knowledge in empirical contexts, i. e. those contexts that affect the (physical) world immediately surrounding us ("physical space" Hempel, 1945, "problems from the real word" Pollak & Garfunkel, 2014). This is done in a presentation of theoretical aspects with historical references and then on a case study on probability calculation (8th grade of a secondary school), in order to address a discussion regarding a "science-oriented direction that is aimed at the development of mathematical theories from real contexts" (Kaiser et al., 2015, p. 361, translated by the authors).